COMBINING THE BEST OF BOTH WORLDS - Khadija Qamar (Army Medical College Rawalpindi, 2021)
Panacea erupted by COVID-19 outbreak has transformed our personal and political perspectives, on priorities and mode of lives, around the world. On March 11, 2020, WHO declaring it as a pandemic followed by nation wide smart lockdown and implementation of social distancing, has remodeled our sociocultural and academic norms. To our interest, it has encouraged medical colleges of our country to take a giant leap from a traditional face-to-face instruction to online learning. Though sudden, massive, and unplanned transition it might be, this not only changed mode of curricular delivery, but uncovered opportunity of grooming ourselves to Millennial expectations. Initially, our digital recluse faculty had to learn basics of computer to become digital refugees. Later, they successfully adapted themselves as digital immigrants to teach a digital native generation!